1993
DOI: 10.1111/j.1365-2478.1993.tb00872.x
|View full text |Cite
|
Sign up to set email alerts
|

DETERMINATION OF ELECTRICAL PROPERTIES OF THE GROUND AT SHALLOW DEPTH WITH AN ELECTROSTATIC QUADRUPOLE: FIELD TRIALS ON ARCHAEOLOGICAL SITES1

Abstract: TABBAGH, A., HESSE, A. and GRARD R. 1993. Determination of electrical properties of the ground at shallow depth with an electrostatic quadrupole: field trials on archaeological sites. Geophysical Prospecting 41,579-597.Knowledge of both the electrical resistivity p and the dielectric permittivity E of the ground is important for the determination of characteristics such as granularity, porosity, moisture and salt content. Whereas the measurement of p is very common and can be achieved using either the d.c. res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
1
5

Year Published

1994
1994
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 13 publications
4
51
1
5
Order By: Relevance
“…For the selected frequency of 15 kHz and the range of parameter values considered in this study, we have found the variation of the complex potential with relative permittivity to be negligible in the range between ε r = 1 (free space) and ε r = 80 (water). Previous studies have shown that a measurable variation of the CR transfer impedance with ε r at audio frequencies can be obtained in highly resistive environments only (Grard and Tabbagh, 1991;Tabbagh et al, 1993).…”
Section: Variation With Electrical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…For the selected frequency of 15 kHz and the range of parameter values considered in this study, we have found the variation of the complex potential with relative permittivity to be negligible in the range between ε r = 1 (free space) and ε r = 80 (water). Previous studies have shown that a measurable variation of the CR transfer impedance with ε r at audio frequencies can be obtained in highly resistive environments only (Grard and Tabbagh, 1991;Tabbagh et al, 1993).…”
Section: Variation With Electrical Propertiesmentioning
confidence: 99%
“…However, as previously discussed, it is unlikely that reliable estimates of ε r can be obtained by low-frequency electromagnetic methods. Determination of ε r with the CR technique may be possible at higher frequencies and in highly resistive geological environments (Tabbagh et al, 1993).…”
Section: The Reverse Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…This "electrostatic formalism" yields a phase-sensitive expression for apparent resistivity which can be shown to reduce to the classical DC expression for the in-phase component of the transfer impedance (Tabbagh et al, 1993;Kuras, 2002):…”
Section: The Capacitive Resistivity (Cr) Techniquementioning
confidence: 99%
“…This article presents therefore a new instrument, an electrostatic multipole, to assess non-destructive and instantaneous estimations of plant water content. This instrument was first designed for geophysical prospecting, especially for archaeology [20]. It has recently been adapted for agronomic research and a first feasibility study has shown that this instrument is sensitive to plant water content [7].…”
Section: Introductionmentioning
confidence: 99%